NiTe1-x-CoTe1-x / NPFC composite material as well as preparation method and application thereof
By loading Ni(OH)2-Co(OH)2 on Te nanorods and calcining to form NiTe1-x-CoTe1-x/NPFC composite, the problems of insufficient conductivity and reactivity of existing electrode materials are solved, and excellent electrochemical performance and high cycling stability are achieved.
Patent Information
- Application Number
- CN202411908995.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-25
AI Technical Summary
Existing electrode materials and electrocatalysts have problems such as low conductivity, large reaction volume changes, slow ion diffusion and few reactive sites, resulting in poor performance in hydrogen electrolysis and supercapacitors.
The NiTe1-x-CoTe1-x/NPFC composite was synthesized by the sacrificial template method, and Ni(OH)2-Co(OH)2 was loaded on the Te nanorod by ionic liquid doping. After calcination, a hollow structure was formed to enhance the specific surface area and conductivity of the material.
It improves electrochemical performance and cycle stability, enhances reaction kinetics and proton collection capabilities, and is suitable for positive electrode materials for flexible solid supercapacitors.
Smart Images

Figure CN119694800A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrode materials, and in particular to a NiTe 1-x -CoTe 1-x / NPFC composite material and its preparation method and application. Background Art
[0002] The intensifying energy crisis and environmental pollution have stimulated research on sustainable renewable energy materials and advanced energy storage devices. Hydrogen, as a clean energy source, is considered to be a promising alternative to fossil fuels, thus attracting the attention of researchers. Water electrolysis is a simple method to produce high-purity hydrogen, but the best performing platinum-based electrocatalysts have the problems of high cost and platinum scarcity. In addition, due to their low cost, fast charge and discharge process, and long cycle stability, supercapacitors have become promising energy storage devices to meet the growing needs. Despite this, the energy density of supercapacitors still cannot meet people's needs. Therefore, the development of functional materials with excellent performance is still one of the difficulties that need to be solved at present.
[0003] Low conductivity, large volume changes during reactions, slow ion diffusion, and few reactive sites are common problems in current electrode materials and electrocatalysts. As an important member of transition metal chalcogenides (TMCs), transition metal tellurides (TMTs) have attracted much attention in recent years due to their structural diversity and unique electronic states. In addition, compared with single metal tellurides, the synthesis of bimetallic telluride heterojunctions generally exhibits good electrochemical performance because different metal ions produce a synergistic effect through chemical bonds. First, the interfacial coupling between various phases with different energy levels leads to changes in the interfacial electronic structure, resulting in a built-in electric field and two opposite charge distribution regions at the heterojunction interface. The generated built-in electric field greatly accelerates the ion migration speed driven by Coulomb force, thereby promoting fast reaction kinetics and greatly reducing ion diffusion resistance. Secondly, heterogeneous composites with rich boundaries present optimized functionality, which can greatly alleviate capacity fading. Studies have shown that the reactivity of metal chalcogenides is positively correlated with the covalency of metal chalcogenides. Therefore, TMT materials should be more ideal electrocatalysts than other chalcogenides. However, most of the reported TMTs still exhibit unsatisfactory electrocatalytic performance to date, which is far inferior to the corresponding sulfides and selenides. Therefore, finding suitable optimization methods to enhance the catalytic and energy storage capabilities of tellurides is urgent but still challenging. Summary of the invention
[0004] The object of the present invention is to provide a NiTe 1-x -CoTe 1-x / NPFC composite material, which is a composite of NiTe-CoTe heterojunction rich in Te vacancies and N, P, and F co-doped carbon, and has excellent electrochemical performance and high cycle stability.
[0005] Another object of the present invention is to provide a NiTe 1-x -CoTe 1-x The preparation method of the / NPFC composite material adopts a sacrificial template method, uses ionic liquid as a dopant, loads Ni(OH)2-Co(OH)2-IL on Te nanorods, and obtains a hollow structure NiTe after calcination. 1-x -CoTe 1-x / NPFC composite materials. The method is simple to operate and has controllable parameters, and is suitable for industrial large-scale production.
[0006] The third object of the present invention is to provide NiTe 1-x -CoTe 1-x Application of / NPFC composite materials as positive electrode materials in flexible solid-state supercapacitors.
[0007] The present invention solves the technical problem by adopting the following technical solutions.
[0008] The present invention proposes a NiTe 1-x -CoTe 1-x The preparation method of the NPFC composite material comprises the following steps: S1, synthesis of tellurium (Te) nanorods; S2, adding Co(NO3)2∙6H2O, Ni(NO3)2∙6H2O, urea, C6H8O7∙H2O, citric acid and the tellurium nanorods into deionized water, heating, cooling, washing and dehumidifying to obtain Ni(OH)2-Co(OH)2-IL / Te; S3, the Ni(OH)2-Co(OH)2-IL / Te is calcined to obtain NiTe 1-x -CoTe 1-x / NPFC composite materials.
[0009] The present invention proposes a NiTe 1-x -CoTe 1-x / NPFC composite material, which is prepared according to the above preparation method.
[0010] The present invention proposes the NiTe 1-x -CoTe 1-x Application of / NPFC composite materials as positive electrode materials in flexible solid-state supercapacitors.
[0011] NiTe of the present invention 1-x-CoTe 1-x The beneficial effects of the NPFC composite material and its preparation method and application are: 1. After calcination by the sacrificial template method, the hollow structure formed by the evaporation of Te nanorods can obtain a larger specific surface area and form Te vacancy defects, so there are more reaction sites and better conductive channels in the electrochemical process, further improving the electrochemical performance.
[0012] 2. The present invention introduces B, N and F into carbon materials through ionic liquid (IL), which can improve the conductivity of the material and enhance the electronegativity, thereby improving the NiTe 1-x -CoTe 1-x / NPFC has the ability to collect more protons. At the same time, the carbon coating can also prevent the material from undergoing a large volume expansion during the electrochemical reaction and improve the cycle stability.
[0013] 3.NiTe 1-x -CoTe 1-x The charge transfer at the NPFC / heterojunction interface leads to the redistribution of electrons, which adjusts the electronic structure of each component, improves the reaction kinetics, and promotes the performance of HER and supercapacitor. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0015] Figure 1 NiTe of Example 1 of the present invention 1-x -CoTe 1-x / NPFC composite material preparation flow chart; Figure 2 The Te nanorods, Ni(OH)2-Co(OH)2-IL / Te and NiTe in Example 1 of the present invention are 1-x -CoTe 1-x Scanning electron microscopy images of / NPFC composites; Figure 3 NiTe of Example 1 of the present invention 1-x -CoTe 1-x HRTEM image of / NPFC composites; Figure 4 NiTe of Example 1 of the present invention 1-x -CoTe 1-x / Element distribution diagram of NPFC composites; Figure 5 NiTe of Example 1 of the present invention 1-x -CoTe 1-x XRD patterns of / NPFC composites; Figure 6 NiTe of Example 1 of the present invention 1-x -CoTe 1-x NiTe / NPFC composites 1-x and CoTe 1-x The differential charge diagram of Figure 7 NiTe of Example 1 of the present invention 1-x -CoTe 1-x GCD curve of / NPFC composite material. DETAILED DESCRIPTION
[0016] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0017] The following is a description of the NiTe 1-x -CoTe 1-x / NPFC composite material and its preparation method and application are specifically described.
[0018] A NiTe provided by an embodiment of the present invention 1-x -CoTe 1-x The preparation method of the NPFC composite material comprises the following steps: S1. Synthesis of tellurium nanorods.
[0019] Further, in a preferred embodiment of the present invention, the step of synthesizing tellurium nanorods is: after adding ascorbic acid and hexadecyltrimethylammonium bromide to distilled water, adding Na2TeO3 and stirring for 25-35 minutes and transferring to an autoclave lined with tellurium, the tellurium nanowire suspension obtained after heating is centrifuged and redispersed to obtain the tellurium nanorods. Specifically, the tellurium nanowire suspension is centrifuged at 10,000 rpm for 10 minutes and then redispersed in distilled water to obtain the tellurium nanorods.
[0020] Furthermore, in a preferred embodiment of the present invention, the mass volume ratio of the ascorbic acid, the cetyltrimethylammonium bromide, the distilled water and the Na2TeO3 is 19~20:1.5~2.5:570~580:1 (g / g / mL / g).
[0021] Furthermore, in a preferred embodiment of the present invention, the heating temperature is 85-95° C., and the heating time is 22-26 hours. Preferably, the heating temperature is 90° C., and the heating time is 24 hours.
[0022] S2, Co(NO3)2∙6H2O, Ni(NO3)2∙6H2O, urea, C6H8O7∙H2O, citric acid and the tellurium nanorods are added to deionized water, and after heating, cooled, washed and dehumidified, Ni(OH)2-Co(OH)2-IL / Te is obtained. The present invention uses ionic liquid as a dopant to load Ni(OH)2-Co(OH)2-IL on Te nanorods, and obtains hollow NiTe after calcination. 1-x -CoTe 1-x / NPFC. Ionic liquid (IL) is a compound composed of organic cations and organic or inorganic anions. It is a "green solvent" due to its non-flammability, high chemical stability, recyclability and non-toxicity. In addition, ionic liquids can be used as dopants, and the elements N, S, F, P, B and other elements in the anions can adjust the physical and chemical properties of the substrate. The present invention introduces B, N and F into the carbon material through IL, which can improve the conductivity of the material and enhance the electronegativity, thereby improving the NiTe 1-x -CoTe 1-x / NPFC has the ability to collect more protons. At the same time, the carbon coating can also prevent the material from undergoing a large volume expansion during the electrochemical reaction and improve the cycle stability.
[0023] Furthermore, in a preferred embodiment of the present invention, the mass volume ratio of the Co(NO3)2∙6H2O, the Ni(NO3)2∙6H2O, the urea, the C6H8O7∙H2O, the citric acid, the tellurium nanorods and the deionized water is 1.7~2.7:1.7~2.7:3.3~4.3:0.8~1.8:1.6~2.6:0.8~1.8 (g / g / mL / g / g / g).
[0024] Furthermore, in a preferred embodiment of the present invention, the heating temperature is 145-155° C., and the heating time is 22-26 hours. Preferably, the heating temperature is 150° C., and the heating time is 24 hours.
[0025] Furthermore, in a preferred embodiment of the present invention, ethanol and deionized water are used for washing, the dehumidification temperature is 65-75° C., and the dehumidification time is 22-26 hours.
[0026] S3, the Ni(OH)2-Co(OH)2-IL / Te is calcined to obtain NiTe 1-x -CoTe 1-x / NPFC composite materials. Vacancies can extend the distance or spacing of active sites, thereby forming a favorable adsorption of OH- / H*. The charge density between the active sites and adjacent coordinating atoms will be redistributed, thereby optimizing the adsorption / desorption of intermediates. The unique local structure induced by vacancies promotes the charge transfer rate and redox kinetics during electrocatalysis and energy storage. After calcination by the sacrificial template method, the hollow structure formed by the evaporation of Te nanorods in the present invention can obtain a larger specific surface area, and at the same time, Te vacancy defects are formed, so that there can be more reaction sites and better conductive channels in the electrochemical process, thereby improving the electrochemical performance.
[0027] Furthermore, in a preferred embodiment of the present invention, the step of calcining the Ni(OH)2-Co(OH)2-IL / Te is as follows: placing the Ni(OH)2-Co(OH)2-IL / Te in a tube furnace, introducing nitrogen, and calcining the Ni(OH)2-Co(OH)2-IL / Te for 2 min s -1 The NiTe 1-x -CoTe 1-x / NPFC composite materials.
[0028] The present invention rationally integrates tellurium vacancies, heterogeneous interfaces and heteroatom doping, and synthesizes a composite of NiTe-CoTe heterojunction rich in Te vacancies and N, P, and F co-doped carbon (NiTe 1-x -CoTe 1-x / NPFC). First, after calcination by sacrificial template method, the hollow structure formed by evaporation of Te nanorods can obtain a larger specific surface area, and at the same time form Te vacancy defects, so there are more reaction sites and better conductive channels in the electrochemical process, further improving the electrochemical performance. Secondly, the introduction of B, N and F into carbon materials through IL can improve the conductivity of the material and enhance the electronegativity, thereby improving the generated NiTe 1-x -CoTe 1-x / NPFC has the ability to collect more protons. At the same time, the carbon coating can also prevent the material from undergoing a large volume expansion during the electrochemical reaction and improve the cycle stability. In addition, NiTe 1-x -CoTe 1-x Charge transfer at the / NPFC heterojunction interface leads to electron redistribution, thereby adjusting the electronic structure of each component and promoting the performance in supercapacitors. The present invention provides important insights into the design of telluride heterojunctions and N, P, F-doped carbon composites with tellurium vacancies, and this optimization approach can also be applied to other types of electrode materials and electrocatalysts.
[0029] The present invention also provides a NiTe 1-x -CoTe 1-x / NPFC composite material, which is prepared according to the preparation method. The present invention adopts ionic liquid to assist in the synthesis of vacancy-rich and multi-element doped materials, and the composite material has excellent electrochemical performance and high cycle stability.
[0030] The present invention also provides the NiTe 1-x -CoTe 1-x / NPFC composite materials as positive electrode materials in flexible solid-state supercapacitors. In supercapacitor tests, NiTe 1-x -CoTe 1-x / NPFC as a cathode material exhibits excellent performance in flexible solid-state supercapacitors at 1.0 A g -1 The specific capacity is 691 C g -1 .
[0031] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0032] Example 1 Reference Figure 1 As shown, this embodiment provides a NiTe 1-x -CoTe 1-x / NPFC composite material, which is prepared according to the following steps: (1) Synthesis of Te nanorods: 1.0 g of ascorbic acid (99%, Macklin, China) and 0.1 g of hexadecyltrimethylammonium bromide (99%, Aladdin, China) were added to a glass beaker containing 30 mL of distilled water. Then 0.052 g of Na2TeO3 (97%, Aladdin, China) was added and magnetically stirred for 30 min. Finally, the solution was transferred to a 50 mL Te-lined autoclave and heated in an oven at 90 °C for 24 h. The obtained Te nanowire suspension was centrifuged at 10,000 rpm for 10 min and then redispersed in 10 mL of distilled water to form Te nanorods.
[0033] (2) Synthesis of Ni(OH)2-Co(OH)2-IL / Te: 100 mg Co(NO3)2∙6H2O, 100 mg Ni(NO3)2∙6H2O, urea (0.2 g), C6H8O7∙H2O (0.05 g), citric acid (0.1 g) and Te nanorods (0.04 g) were added to deionized water (60 mL). The solution was heated at 150 °C for 24 h. After cooling to room temperature, the material was repeatedly washed with ethanol and deionized water, and then dehumidified at 70 °C for 24 h to obtain Ni(OH)2-Co(OH)2-IL / Te.
[0034] (3) NiTe 1-x -CoTe 1-x Synthesis of / NPFC: 50 mg Ni(OH)2-Co(OH)2-IL / Te was placed in a tube furnace and nitrogen was introduced. -1 The sample was heated to 400°C at a heating rate of 100°C and kept warm for 2 hours. After cooling to room temperature, the sample was taken out and centrifuged three times in deionized water to obtain the final sample NiTe 1-x -CoTe 1-x / NPFC composite materials.
[0035] Example 2 In this embodiment, a NiTe 1-x -CoTe 1-x / NPFC composite material, which is prepared according to the following steps: (1) Synthesis of Te nanorods: 1.0 g of ascorbic acid (99%, Macklin, China) and 0.1 g of hexadecyltrimethylammonium bromide (99%, Aladdin, China) were added to a glass beaker containing 30 mL of distilled water. Then 0.052 g of Na2TeO3 (97%, Aladdin, China) was added and magnetically stirred for 30 min. Finally, the solution was transferred to a 50 mL Te-lined autoclave and heated in an oven at 85 °C for 26 h. The obtained Te nanowire suspension was centrifuged at 10,000 rpm for 10 min and then redispersed in 10 mL of distilled water to form Te nanorods.
[0036] (2) Synthesis of Ni(OH)2-Co(OH)2-IL / Te: 100 mg Co(NO3)2∙6H2O, 100 mg Ni(NO3)2∙6H2O, urea (0.2 g), C6H8O7∙H2O (0.05 g), citric acid (0.1 g) and Te nanorods (0.04 g) were added to deionized water (60 mL). The solution was heated at 150 °C for 24 h. After cooling to room temperature, the material was repeatedly washed with ethanol and deionized water, and then dehumidified at 70 °C for 24 h to obtain Ni(OH)2-Co(OH)2-IL / Te.
[0037] (3) NiTe 1-x -CoTe 1-x Synthesis of / NPFC: 50 mg Ni(OH)2-Co(OH)2-IL / Te was placed in a tube furnace and nitrogen was introduced. -1 The sample was heated to 400°C at a heating rate of 100°C and kept warm for 2 hours. After cooling to room temperature, the sample was taken out and centrifuged three times in deionized water to obtain the final sample NiTe 1-x -CoTe 1-x / NPFC composite materials.
[0038] Test Example 1 In this example, a scanning electron microscope was used to observe the Te nanorods, Ni(OH)2-Co(OH)2-IL / Te and NiTe in Example 1. 1-x -CoTe 1-x / NPFC composite materials were observed.
[0039] like Figure 2 The Te nanorods, Ni(OH)2-Co(OH)2-IL / Te and NiTe in Example 1 are shown. 1-x -CoTe 1-x Scanning electron microscope image of / NPFC composite material. Figure 2 (a) Scanning electron microscopy image of Te nanorods; Figure 2 (b) is a scanning electron micrograph of Ni(OH)2-Co(OH)2-IL / Te; Figure 2 (c) NiTe 1-x -CoTe 1-x Scanning electron micrograph of / NPFC composite material. Figure 2 It can be seen that the length of the Te nanorods synthesized by the hydrothermal method is about 1.5~2.5μm ( Figure 2 (a)). By adding ionic liquid, nickel salt and cobalt salt, Ni(OH)2-Co(OH)2-IL complex was grown outside Te nanorods after solvothermal method, showing a needle-like structure ( Figure 2 (b) After calcination, the Te nanorods melt and form a hollow structure inside the Ni(OH)2-Co(OH)2-IL, generating a heterojunction NiTe containing Te vacancies. 1-x -CoTe 1-x , wrapped in C co-doped with N, P, and F elements ( Figure 2 c).
[0040] Test Example 2 In this example, a projection electron microscope was used to examine the NiTe 1-x -CoTe 1-x / NPFC composite materials were observed.
[0041] like Figure 3 The NiTe of Example 1 is shown. 1-x -CoTe 1-x HRTEM image of / NPFC composite material. Figure 3 It can be seen that the lattice fringes, Te vacancies and amorphous carbon of the heterojunction NiTe / CoTe can be clearly observed in the magnified TEM image. According to the PDF card and lattice fringes, it can be analyzed that the crystal plane with a lattice spacing of 2.10 nm corresponds to the (002) crystal plane of NiTe, and the crystal plane with a lattice spacing of 2.68 nm corresponds to the (102) crystal plane of CoTe.
[0042] Test Example 3 This test example is based on the NiTe 1-x -CoTe 1-x / NPFC composite materials were subjected to element distribution spectrum analysis.
[0043] like Figure 4 The NiTe of Example 1 is shown. 1-x -CoTe 1-x Element distribution diagram of / NPFC composite materials. Figure 4 It can be seen that Ni, Co, Te, N, P, F, and C elements are present in NiTe 1-x -CoTe 1-x / Evenly distributed in NPFC.
[0044] Test Example 4 In order to 1-x -CoTe 1-x / NPFC composite material was analyzed for components. In this example, the NiTe 1-x -CoTe 1-x The crystal phase and crystal structure of the / NPFC composite material were tested by XRD. Figure 5 The NiTe of Example 1 is shown. 1-x -CoTe1-x XRD pattern of / NPFC composite material. Figure 5 It can be seen that by comparing and analyzing the PDF cards, NiTe 1-x -CoTe 1-x The peaks of / NPFC can be assigned to NiTe (00-038-1393) and CoTe (03-034-0420).
[0045] Test Example 5 like Figure 6 The NiTe of Example 1 is shown. 1-x -CoTe 1-x NiTe / NPFC composites 1-x and CoTe 1-x The differential charge diagram of this test example is shown in Figure 2. The model was established based on the component structure of the material, where the detailed models of NiTe1-x-CoTe1-x / NPFC, NiTe-CoTe / C, CoTe / C, and NiTe / C are shown in Figure 2. Figure 6 As shown in the analysis of differential charge, it can be seen that the formation of heterojunction and the recombination of heterojunction and NPFC can redistribute NiTe 1-x -CoTe 1-x / NPFC atomic surface charge, which is also the NiTe 1-x -CoTe 1-x / The reason why the performance of NPFC is higher than that of the comparison material.
[0046] Test Example 6 This test example uses NiTe 1-x -CoTe 1-x The / NPFC composite material was used as a positive electrode material for supercapacitor testing. The specific steps are as follows: The electrode material, carbon black and polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 7:2:1 and made into a slurry with N-methylpyrrolidone (NMP). Subsequently, the obtained slurry was covered on nickel foam as a working electrode. All electrochemical experiments related to supercapacitors were carried out in 3.0 M KOH solution, with platinum sheet as the counter electrode and Hg / HgO as the reference electrode. GCD measurements were performed using an electrochemical workstation (CHI760e, CH Instruments).
[0047] like Figure 7 The NiTe of Example 1 is shown. 1-x -CoTe 1-x / NPFC composite material constant current charge / discharge (GCD) curve. Figure 7 It can be seen that NiTe 1-x -CoTe 1-x / NPFC in supercapacitor test, at 1.0 A g -1 The specific capacity is 691 C g -1 .
[0048] The embodiments described above are part of the embodiments of the present invention, rather than all of the embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
Claims
1. A NiTe 1-x -CoTe 1-x A method for preparing a / NPFC composite material, characterized in that: The following steps are involved: S1, synthesis of tellurium nanorods; S2, adding Co(NO3)2∙6H2O, Ni(NO3)2∙6H2O, urea, C6H8O7∙H2O, citric acid and the tellurium nanorods into deionized water, heating, cooling, washing and dehumidifying to obtain Ni(OH)2-Co(OH)2-IL / Te; S3, the Ni(OH)2-Co(OH)2-IL / Te is calcined to obtain NiTe 1-x -CoTe 1-x / NPFC composite materials.
2. The preparation method according to claim 1, characterized in that In step S1, the steps of synthesizing tellurium nanorods are: after adding ascorbic acid and cetyltrimethylammonium bromide to distilled water, adding Na2TeO3 and stirring for 25-35 minutes and transferring to an autoclave lined with tellurium, the tellurium nanowire suspension obtained after heating is centrifuged and redispersed to obtain the tellurium nanorods.
3. The preparation method according to claim 2, characterized in that: The mass volume ratio of the ascorbic acid, the cetyltrimethylammonium bromide, the distilled water and the Na2TeO3 is 19-20:1.5-2.5:570-580:1 (g / g / mL / g).
4. The preparation method according to claim 2, characterized in that: In step S1, the heating temperature is 85-95° C. and the heating time is 22-26 hours.
5. The preparation method according to claim 1, characterized in that: In step S2, the mass volume ratio of the Co(NO3)2∙6H2O, the Ni(NO3)2∙6H2O, the urea, the C6H8O7∙H2O, the citric acid, the tellurium nanorods and the deionized water is 1.7~2.7:1.7~2.7:3.3~4.3:0.8~1.8:1.6~2.6:0.8~1.8 (g / g / mL / g / g / g).
6. The preparation method according to claim 1, characterized in that: In step S2, the heating temperature is 145-155° C., and the heating time is 22-26 hours.
7. The preparation method according to claim 1, characterized in that: In step S2, ethanol and deionized water are used for washing, the dehumidification temperature is 65-75° C., and the dehumidification time is 22-26 hours.
8. The preparation method according to claim 1, characterized in that In step S3, the step of calcining the Ni(OH)2-Co(OH)2-IL / Te is as follows: placing the Ni(OH)2-Co(OH)2-IL / Te in a tube furnace, introducing nitrogen, and calcining the Ni(OH)2-Co(OH)2-IL / Te for 2 min s -1 The NiTe 1-x -CoTe 1-x / NPFC composite materials.
9. A NiTe 1-x -CoTe 1-x / NPFC composite material, characterized in that Prepared according to the preparation method according to any one of claims 1 to 8.
10. NiTe according to claim 9 1-x -CoTe 1-x Application of / NPFC composite materials as positive electrode materials in flexible solid-state supercapacitors.